Profil FTIR, kandungan fenolik, dan aktivitas penangkapan radikal bebas ekstrak daun talas beneng (Xanthosoma undipes K. Koch) dari pelarut dengan polaritas yang berbeda - Mohamad Ana Syabana; Septariawulan Kusumasari; Yonida Salsabila; Winda Nurtiana (AGROINTEK, 2024)
Beneng taro leaves (Xanthosoma undipes K. Koch) are Banten's local biodiversity, which has recently been used as a substitute for tobacco in cigarettes. The availability of this commodity is abundant along with increased the planted area. Therefore, it is necessary to evaluate other potency such as functional activities and also their phytochemical profiles which have not reported yet. One of importance factors that influencing functional and phytochemical profiles is the polarity of extraction solvent. The purpose of this study was to analyze the chemical profile and free radical scavenging activity of beneng taro leaves extracted with various polarities solvent. The leaves extraction was carried out using non-polar, semi-polar and polar solvents, namely hexane, chloroform, acetone and water. Their phytochemical profile was conducted by analyzing total phenolic content and FTIR spectrum, while functional activities by determining free radical scavenging activity. The results showed that the highest phenolic content was obtained from chloroform extract, while the free radical scavenging activity (IC50) was acquired from acetone extract with values of 11.24 mg GAE/g and 36.83 µg/ml, respectively. The FTIR spectrum of the hexane, chloroform, and acetone extract of beneng taro leaves had similar profiles, while the water extract was different.